Cu3Nb2O8: a multiferroic with chiral coupling to the crystal structure. - Johnson, R; Nair, S; Chapon, L; Bombardi, A; Vecchini, C; Prabhakaran, D; Boothroyd, A; Radaelli, P (2011)
By combining bulk properties, neutron diffraction, and nonresonant x-ray diffraction measurements, we demonstrate that the new multiferroic Cu(3)Nb(2)O(8) becomes polar simultaneously with the appearance of generalized helicoidal magnetic ordering. The electrical polarization is oriented perpendicularly to the common plane of rotation of the spins-an observation that cannot be reconciled with the conventional theory developed for cycloidal multiferroics. Our results are consistent with coupling between a macroscopic structural rotation, which is allowed in the paramagnetic group, and magnetically induced structural chirality.